2023
DOI: 10.1111/bju.15974
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous (idiopathic) rupture of the urinary bladder: a systematic review of case series and reports

Abstract: Objectives To perform a systematic review of all cases of spontaneous rupture of the urinary bladder (SRUB) and to describe the demographic data, associated comorbidities, clinical presentation, diagnosis, relevant laboratory findings, associated factors, management, morbidity and mortality associated with the presentation of SRUB. Methods The study protocol was registered with the International Prospective Register of Systematic Reviews (PROSPERO). A search was carried out across the following electronic data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 248 publications
(243 reference statements)
0
29
0
1
Order By: Relevance
“…In this study, the median age was much younger at 59 years old, and the male‐to‐female ratio was 1.7:1. A review of patients with spontaneous bladder rupture (although excluding bladder cancer patients) found that spontaneous bladder rupture was more common in women 2 . They note vaginal delivery as a risk factor for this 2 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this study, the median age was much younger at 59 years old, and the male‐to‐female ratio was 1.7:1. A review of patients with spontaneous bladder rupture (although excluding bladder cancer patients) found that spontaneous bladder rupture was more common in women 2 . They note vaginal delivery as a risk factor for this 2 .…”
Section: Discussionmentioning
confidence: 99%
“…2 They note vaginal delivery as a risk factor for this. 2 Post-menopause, the bladder can become thinner and lose elasticity in women; a combination of hormonal and post-pregnancy factors may partially account for why there seems to be a proportionally higher number of women in this review of bladder rupture secondary to malignancy. In this review, spontaneous bladder rupture was the first presentation of bladder cancer in most cases.…”
Section: Spontaneous Bladder Rupture Is Generally Distinguished By Ae...mentioning
confidence: 99%
See 2 more Smart Citations
“…UR patients with mental disorders or alcohol abuse sometimes do not complain of voiding difficulties, and sometimes suffer bladder rupture. 1,2 This patient had no such conditions. Absence of renal-dysfunction data and no hydronephrosis suggest that the episode was acute and transient.…”
mentioning
confidence: 89%